Pola Penggunaan dan Rasionalitas Terapi Obat pada Pasien Gagal Jantung Kongestif - Angkasa, Adelya Putri; Wulandari, Prihastini Setyo; Listina, Osie (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2025)
Congestive Heart Failure (CHF) is one of the cardiovascular diseases with high prevalence and significant morbidity and mortality rates, including in RSUD dr. Soeselo Tegal Regency. Rational pharmacotherapy management is crucial to reduce hospitalization rates and improve patient quality of life. This study aims to evaluate the use of drugs in hospitalized CHF patients based on the parameters of correct diagnosis, correct indication, correct drug, and correct dose. The design of this study was descriptive observational with a retrospective approach, using medical record data of CHF patients treated at RSUD Dr. Soeselo Tegal Regency during the period July-December 2023. The samples analyzed were 79 patients. The results showed that the most widely used drug classes were loop diuretics (furosemide), beta-blockers (bisoprolol, carvedilol), aldosterone antagonists (spironolactone), ARBs (candesartan), and ACE-I (ramipril, captopril). The majority of patients received therapy at doses appropriate for standard CHF therapy and the longest inpatient stay was 7 days. The evaluation showed that all patients had received therapy that met the four indicators of rational use of drugs (100% correct diagnosis, 100% correct indication, 100% correct drug, and 100% correct dose). The conclusion of this study indicates that the use of CHF drugs in hospitalized patients at RSUD Dr. Soeselo Tegal Regency has been carried out rationally and in accordance with national therapeutic guidelines